Nonsuicidal Self-Injury Disorder in Adolescents: Clinical Utility of the Diagnosis Using the Clinical Assessment of Nonsuicidal Self-Injury Disorder Index - Zetterqvist, Maria; Perini, Irene; Mayo, Leah M.; Gustafsson, Per A. (Frontiers in Psychiatry, 2020)
Nonsuicidal self-injury disorder (NSSID) is a condition in need of further study, especially in adolescent and clinical populations where it is particularly prevalent and studies are limited. Twenty-nine clinical self-injuring adolescents were included in the study. The Clinical Assessment of Nonsuicidal Self-Injury Disorder Index (CANDI) was used to assess prevalence of NSSID. The NSSID diagnosis criteria were met by 62.1% of adolescents. The impairment or distress criterion was least often met. Criteria B and C (assessing reasons for NSSI and cognitions/emotions prior to NSSI) were confirmed by 96-100% of all participants. Adolescents with NSSI in this clinical sample had several comorbidities and high levels of psychopathology. NSSID occurred both in combination with and independently of borderline personality disorder traits as well as suicide plans and attempts. Those with NSSID had a significantly higher cutting frequency than those not meeting full NSSID criteria. Other NSSI characteristics, comorbidity, psychopathology and trauma experiences did not differ between groups. CANDI was a feasible tool to assess NSSID in adolescents. It is important to use structured measures to assess the validity of the NSSID diagnosis across development in both community and clinical samples. The clinical utility of the NSSID diagnosis is discussed.